Is the methanogenic community reflecting the methane emissions of river sediments?—comparison of two study sites. Issue 4 (16th March 2017) - Chaudhary, Prem Prashant; Rulík, Martin; Blaser, Martin
Abstract: Studies on methanogenesis from freshwater sediments have so far primarily focused on lake sediments. To expand our knowledge on the community composition of methanogenic archaea in river sediments, we studied the abundance and diversity of methanogenic archaea at two localities along a vertical profile (top 50 cm) obtained from sediment samples from Sitka stream (the Czech Republic). In this study, we compare two sites which previously have been shown to have a 10‐fold different methane emission. Archaeal and methanogen abundance were analyzed by real‐time PCR and T‐RFLP. Our results show that the absolute numbers for the methanogenic community (qPCR) are relatively stable along a vertical profile as well as for both study sites. This was also true for the archaeal community and for the three major methanogenic orders in our samples (Methanosarcinales, Methanomicrobiales, and Methanobacteriales). However, the underlying community structure (T‐RFLP) reveals different community compositions of the methanogens for both locations as well as for different depth layers and over different sampling times. In general, our data confirm that Methanosarcinales together with Methanomicrobiales are the two dominant methanogenic orders in river sediments, while members of Methanobacteriales contribute a smaller community and Methanocellales are only rarely present in this sediment. Our results show that the previously observed 10‐fold difference in methane emission of the two sites could not be explained by molecular methods alone. Abstract : We evaluated the abundance a composition of the methanogenic community at different depth of sediment cores of river Sitka, the Czech Republic for a low and a high methane‐emitting site. Our results show, that the methanogenic community is relatively stable while the underlying community structure reveals different community compositions of the methanogens for both locations as well as for different depth layers.